Atypical form of cat scratch disease in immunocompetent patient - Kojić Miroslav; Mikić Dragan; Nožić Darko; Zolotarevski Lidija (Vojnosanitetski Pregled)
Introduction. Cat scratch disease (CSD) is an acute infectious disease with benign course caused by the bacteria Bartonella henselae. Clinically, it is usually manifested as regional lymphadenopathy and mild infective syndrome. Rare forms of the disease which usually occur in immunocompromised presons are: encephalitis, transverse myelitis, neuroretinitis, granulomatosus conjunctivitis, arthritis, hepatitis etc. Case report. We presented an atypical form of cat scratch disease in a young immunocompetent female person. The disease was manifested with prolonged fever, rash, purulent lymphadenitis and hepatitis. The diagnosis was based on characteristic patohystological finding and exclusion of the other causes of lymphadenopathy. The patient was treated by antibiotics for a few weeks, with surgical incision and drainage of the purulent lymphadenitis. Conclusion. Atypical forms of CSD could be an important differential-diagnostic problem, especially if there is no opportunity for serological confirmation of the disease.